النقد التاريخي عند ابن حارث الخشني (ت361هـ/ 972م) في كتابيه "قضاة قرطبة" و"طبقات علماء إفريقية" - زيان, علي (University of Eloued جامعة الوادي, 2021)
تناولت هذه الدراسة موضوع النقد التاريخي عند ابن حارث الخشني (ت361هـ/ 972م) في كتابيه "قضاة قرطبة" و"طبقات علماء إفريقية". فتم التعريف بالمؤلف ونشأته العلمية وشيوخه الذين درس عليهم في افريقية والأندلس، والمناصب التي تقلدها، والمكانة التي حظي بها وأهم المؤلفات التي صنفها. ثم عني البحث بمنهجه النقدي الذي مارسه وهو نوعان، الأول: هو التقويم وإصدار الأحكام على المترجمين سلبا أم إيجابا، والنوع الثاني: هو نقد الروايات التاريخية التي أوردها في الكتابين ورأى فيها مجالا للنقد. الكلمات المفتاحية: الخشني، النقد التاريخي، الرواية، الأندلس، افريقية. Summary This study dealt with the subject of historical criticism according to Ibn Harith Al-Khashni (d. 361 AH / 972 AD) in his books “The Judges of Cordoba” and “Tabaqat African Scholars”. The author, his scientific upbringing, the sheikhs he studied in Africa and Andalusia, the positions he held, the position he received, and the most important works he classified were introduced to the author. Then the research was concerned with its critical approach, which he practiced, and it is of two types, the first: evaluation and passing judgments on translators, negatively or positively, and the second type: criticizing the historical narratives that he mentioned in the two books, and he saw in them an area for criticism.. Keywords: Al-Khishni, historical criticism, the novel, Andalusia, Africa.
مقال